2017
DOI: 10.1002/cpp.2109
|View full text |Cite
|
Sign up to set email alerts
|

Four years comparative follow‐up evaluation of community‐based, step‐down, and residential specialist psychodynamic programmes for personality disorders

Abstract: Although the fulcrum of service provision for personality disorder (PD) has shifted from hospital-based to psychodynamically- and cognitively-oriented outpatient programmes, very few studies have attempted to compare specialist moderate intensity outpatient programmes with specialist high-intensity residential models, or to explore whether a period of inpatient treatment may be necessary to improve outcome and prognosis. In this article, we prospectively compare changes over a 4-year period in 3 groups of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Step‐down facilities post‐admission (i.e. outpatient therapy and outreach nursing) significantly improved outcomes, and at 4‐year follow‐up, the benefits were maintained …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Step‐down facilities post‐admission (i.e. outpatient therapy and outreach nursing) significantly improved outcomes, and at 4‐year follow‐up, the benefits were maintained …”
Section: Introductionmentioning
confidence: 96%
“…outpatient therapy and outreach nursing) significantly improved outcomes, 4 and at 4-year followup, the benefits were maintained. 5 Specific psychological interventions for BPD have been examined, with randomized controlled trials showing the effectiveness of mentalizationbased treatment, 6,7 dialectical behaviour therapy 8 and systems training for emotional predictability and problem solving. 9 However, those diagnosed with BPD may not meet the criteria for specialized therapy.…”
Section: Introductionmentioning
confidence: 99%
“…By bringing together multiple types of intervention, integrative group treatment offers a fertile environment in which patients may address social functioning difficulties (Chiesa, Cirasola, & Fonagy, ). Indeed, intensive day treatment has been found to promote improvement in social role and health‐related quality of life among patients with personality dysfunction (Horn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Effect sizes were further reduced when publication bias was taken into account, inviting caution when considering the results of these specialized treatment approaches. In addition, only a handful of studies have investigated the clinical efficacy of residential models versus less intensive approaches for PD (Bartak et al, 2010(Bartak et al, , 2011Chiesa et al, 2017). Although changes in mentalizing have been suggested to be a common factor underpinning symptomatic improvements and changes in functioning in all these contexts (Bateman, Campbell, Luyten, & Fonagy, 2018;Goodman, 2013;Montgomery-Graham, 2016), there is a dearth of research with regard to the evaluation of improvement in RF as a result of these different treatment approaches and the association between clinical changes and changes in RF in samples of patients with PD.…”
mentioning
confidence: 99%
“…Several studies have shown that day-hospital and outpatient specialist approaches based on mentalization-based treatment (Bateman & Fonagy, 2009; Gullestad et al, 2012; Laurenssen et al, 2018), transference-focused psychotherapy (Clarkin, Levy, Lenzenweger, & Kernberg, 2007; Doering et al, 2010), a modified form of cognitive–behavioral therapy (DeCou, Comtois, & Landes, 2019; McMain, Guimond, Streiner, Cardish, & Links, 2012; Mehlum et al, 2016; Neacsiu, Bohus, & Linehan, 2014), schema-focused therapy (Sempértegui, Karreman, Arntz, & Bekker, 2013), and community-based psychosocial (CBP) treatment (Chiesa, Cirasola, & Fonagy, 2017; Chiesa, Fonagy, & Gordon, 2009) are promising treatment approaches in improving a number of clinical outcomes in a range of PDs. However, a recent meta-analysis (Cristea et al, 2017) of 33 randomized controlled trials found small to moderate differences in effectiveness between specialized psychotherapy and nonspecialized treatment in improving PD outcomes.…”
mentioning
confidence: 99%